ANALISIS BREAK EVEN POINT PADA USAHA KERUPUK SINGKONG UD KELOMPOK TANI KULIM UNGGUL KELURAHAN KULIM KOTA PEKANBARU - Hutani, Sulina Surika Hutani Surika; Harya, Gani Harya; ', Caska (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The company's goal in the operations is to gain profit / gain. The size of the profit gained often becomes a measure of success or failure of the company's management. Conditions up down experienced a small business and industry can be a factor affecting the smooth operation of the profit operasinya.perencanaan require tools such as break-even point analysis to study the relationship between fixed costs, variable costs, profits and sales volume, resulting in an industry should strive as much as possible to avoid loss or break-even situation. Crackers attempt Cassava Farmers Group Kulim Unngul UD is small and medium businesses that sell cassava crackers. This study aimed to analyze the break even point at Crackers Cassava Enterprises Kulim Unggul UD Farmers Group. The method used is descriptive analysis method, to get a clearer picture and detailed based on the data and information obtained .. The data used are secondary data is data of fixed costs, variable costs, sales volume and selling prices. The results showed Crackers Cassava Enterprises Kulim Unggul UD Farmers Group has been able to optimize performance so already gained sales above break even. Cassava Crackers attempt Kulim Tani Unggul UD group should perform the classification of expenses based on the cost of the required behavior in planning a better profit. Keywords : break even point, fixed costs, variable costs. Â  Â